2022
DOI: 10.2478/mgr-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Discordant agendas on a just transition in Romanian coal mining areas: The case of the Jiu Valley

Abstract: Despite the promises that the just transition will bring more democracy and prosperity, there are legitimate fears that, in some regions, the pre-existing inequalities will be reinforced rather than rectified. Questioning how community resilience can be stimulated prior to and during coal mining closures, this paper focuses on Jiu Valley, a coal mining region in Romania. Using empirical and action research methodologies, this case study underlines the importance of considering the level of agency and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In contrast, as this paper argues, it is important to also account for contexts in which the finances are available, which is harder to do, and yet institutional capacity or consensus on how to utilize them is not. Facing the same challenges, and having access to similar financial resources, communities still achieve different results in managing the energy transition, because they possess different local capabilities (Nicola and Schmitz, 2022).…”
Section: Literature Review: European Investor State and The Just Tran...mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, as this paper argues, it is important to also account for contexts in which the finances are available, which is harder to do, and yet institutional capacity or consensus on how to utilize them is not. Facing the same challenges, and having access to similar financial resources, communities still achieve different results in managing the energy transition, because they possess different local capabilities (Nicola and Schmitz, 2022).…”
Section: Literature Review: European Investor State and The Just Tran...mentioning
confidence: 99%
“…With a total population of approximately 132,000 inhabitants, the micro-region is currently facing uncertainty about what will happen after the closure of the last four coal mines. However, in the framework described by the European Commission as a Just Transition, Jiu Valley has, at least theoretically, the prospect of a bounce back, if local stakeholders agree upon sustainable development projects that will attract solid investments (Nicola and Schmitz, 2022).…”
Section: Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of Romania, the inability to convert the post-industrial territories has already generated massive emigration, millions of Romanians originating from deindustrialised areas finding a better standard of living in other EU member states [26]. As for those remaining in the increasingly depopulated regions, they are currently trying to take advantage of the opportunities offered by the sustainability policies imposed at the European level, tourism being considered by many local stakeholders as a viable post-mining development track [27]. Focusing on a case study from Andalusia (Spain), Bahamonde-Rodriguez et al [28] highlighted the stigma that this region carried long after the cessation of mining and suggested that improving the image of such territories is a pre-condition to access new development paths.…”
Section: Challenges In Transforming Post-mining Regions Into Tourist ...mentioning
confidence: 99%